Normative patterns and factors associated with presbyopia progression in a multiethnic Asian population: the Singapore Epidemiology of Eye Diseases Study. Issue 11 (12th February 2020) - Majithia, Shivani; Wong, Kah Hie; Chee, Miao Li; Soh, Zhi-Da; Thakur, Sahil; Fang, Xiao Ling; Teo, Zhen Ling; Sabanayagam, Charumathi; Tham, Yih Chung; Cheng, Ching-Yu
Abstract : Background/Aim: To investigate normative patterns and factors associated with presbyopia progression in a multiethnic Asian population. Methods: Malay, Indian and Chinese participants aged 40–80 years who had baseline and 6-year follow-up examinations with subjective refraction data were recruited from the Singapore Epidemiology of Eye Diseases Study. Presbyopia progression was defined as an increase in near addition power of ≥+0.50 dioptre (D) from baseline to follow-up visit. Modified Poisson regression analyses were used to determine baseline factors associated with presbyopia progression. Results: From the eligible 3974 eyes, 2608 eyes were included for final analysis after excluding eyes with a history of cataract surgery (929 eyes) and best-corrected distance visual acuity worse than 20/40 (342 eyes). Overall the mean near addition power change over 6 years was +0.25 D; Malays showed greater change (+0.37 D) compared with Indians (+0.23 D) and Chinese (+0.16 D). After adjusting for baseline age, gender, body mass index, hypertension, cataract, refractive error and daily hours of reading and writing, Malays were more likely to have presbyopia progression compared with Chinese (RR (relative risk)=1.67; 95% CI 1.43 to 1.95; p<0.001) and Indians (RR=1.45; 95% CI 1.25 to 1.68; p<0.001). Individuals aged 60–69 years (RR=0.77; p=0.006) and ≥70 years (RR=0.51; p<0.001) were less likely to progress in presbyopia compared with those aged 40–49. Conclusion: In this Asian population, the near addition power change over 6 years was lower than the current near addition prescription guidelines (+0.25 D vs +0.60 D). Our findings may help update near addition prescription guidelines that can be more tailored to Asians.